Analysis of environmental management practices of Higher Education Institutions - Frizzo, Kamila; Motke, Francies Diego; Machado, Emanuelly Comoretto; Silva, Ygor Cezar; Ávila, Lucas Veiga; Zamberlan, João Fernando (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Environmental management has become an emerging issue that has been increasingly growing in academia and business, which organizations should not only be concerned with meeting standards and laws, but also are seeking to better serve their customers become increasingly more demanding, involving different layers and sectors of society, especially the education sector, such as the Higher Education Institutions (HEI) that are forming professional and have representation in society. Therefore, this study aims to identify the environmental management practices adopted by Higher Education Institutions (HEI) face in the city of Santa Maria / RS. The research is characterized as exploratory and adopted as a method to study multi cases. The main results revealed that environmental management practices adopted by the institutions analyzed are incipient and characterized as isolated as they are implemented only in some sectors of the institution. The results show, lack of awareness and planning managers , lack of a specific industry environmental management , lack of reporting, awareness of green spaces for students, faculty and staff. Once the participating institutions have no environmental certification standard.